Education, training and work : some Commonwealth responses to youth unemployment (Commonwealth Secretariat LondonGB, 1988)
Concentrates on opportunites for education and training outside of school. Aims to review exemplary experiences in a number of Commonwealth countries as a guide for further activity or enquiry.
Keywords: YOUTH